The Preemptive Effect of Magnesium Sulfate Gargle, Ketamine Gargle or Dexamethasone Intravenous Injection on Sore Throat Following Surgery in Patients undergoing Surgery with General Anesthesia - Mohammadreza Safavi; Azim Honarmand; Farid Yaghini (مجله دانشکده پزشکی اصفهان, 2018)
Background: Sore throat is a common complication following surgery. The aim of this study was to determine the preventive effect of magnesium sulfate gargle, ketamine glucose gargle or dexamethasone intravenous injection on postoperative sore throat in patients undergoing general anesthesia and to compare it with the control group.